Self-confidence using technology, understanding of TPACK and teaching quality of physical education’s teacher candidate while online learning - Friskawati, Gita Febria (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
This study aims to reveal the relationship between self-confidence, understanding of TPACK and the teaching quality of prospective physical education teachers when conducting online learning. The correlational research method was used in a population of 132 students practicing STKIP Pasundan who were following the PPL program. A total of 96 samples were involved in this study by means of convenience sampling. The instrument used to measure teaching confidence is a questionnaire with a Likert scale questionnaire (1-5 scale) which has been tested for validity and reliability with the results of r = 0.791. Meanwhile, to measure the quality of teaching, the Teaching Quality Scale (TQS) and TPACK Questioners. The results showed that the contribution of all independent variables (confidence and understanding of TPACK) to the dependent variable (quality of teaching physical education) simultaneously was 72.1%. Research shows that the psychological factor of self-confidence can determine the goals to be achieved (quality of teaching physical education) even though it is weak by being influenced by experience, knowledge and other skills, including understanding of TPACK. Therefore, further research is recommended to discuss forms of intervention for prospective physical education teachers to increase confidence in using technology when teaching online and increase understanding of TPACK in order to make students interested in learning when learning online so as to maintain teaching quality.